2016
DOI: 10.1097/scs.0000000000003029
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soft Tissue Measurements After Mandibular Distraction Osteogenesis

Abstract: Soft tissue changes were observed in all patients. There was highly significant increase in tragus-commissure line in all patients, significant increase in lateral canthus-commissure line in 10 patients, and significant increase in medial canthus-commissure line and lower lip length in 9 patients. The lines' relation with the overjet was highly significant in right side of tragus-commissure line, lateral canthus-commissure line, medial canthus-commissure line, and lower lip length, and significant in left side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Mackool et al 15 analyzed the volume of the medial pterygoid muscle on post-MDO computed tomography scans to demonstrate an average increase of 75% after bilateral mandibular distraction. Others have likewise demonstrated changes in the facial profile related to the anterior displacement of the mandible during MDO with significant increase in distance measured from the tragus to the oral commissure 17 …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Mackool et al 15 analyzed the volume of the medial pterygoid muscle on post-MDO computed tomography scans to demonstrate an average increase of 75% after bilateral mandibular distraction. Others have likewise demonstrated changes in the facial profile related to the anterior displacement of the mandible during MDO with significant increase in distance measured from the tragus to the oral commissure 17 …”
Section: Discussionmentioning
confidence: 90%
“…Others have likewise demonstrated changes in the facial profile related to the anterior displacement of the mandible during MDO with significant increase in distance measured from the tragus to the oral commissure. 17 The specific benefit of mandibular advancement in the PRS population is the associated anterior displacement of the tongue and resultant increase in airway volume. Our previous work showed that the increase in airway size preferentially affects the retropalatal space, which can lead to supraphysiologic airway dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1992, when McCarthy et al reported the successful treatment of HFM patients with mandibular distraction osteogenesis (MDO), it has become an essential tool in treating HFM ( 3 ). MDO not only effectively lengthens the mandibular ramus but also simultaneously lengthens the affected soft tissues, periosteal muscles, intraosseous vessels, and nerves ( 4 ). However, it is not easy to perform accurately, and the postoperative outcome depends on the precise operation.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 En estos RN, la osteogénesis por distracción mandibular (ODM) es una de las principales herramientas reconstructivas en la actualidad, 1,2 que ha demostrado su efectividad para promover el crecimiento y la expansión ósea de la matriz de tejido blando perimandibular, particularmente, en los pacientes pediátricos. 3,4 Se presenta a una paciente RN con VAD secundaria a una malformación craneofacial congénita.…”
Section: Introductionunclassified